The bosses' bonanza - BBC Education & Training (London : BBC Education & Training, 2001)
Britain's top executives have been awarded increasingly lavish and complex remuneration packages in recent months. This program look at the history of executive remuneration and ask why the bosses' bonuses have grown in spite of reforms proposed by three different reports on self-regulation
DVD format
Keywords: Executives -- Salaries, etc. -- Great Britain